Predicting the Development of Gastric Neoplasms in a Healthcare Cohort by Combining Helicobacter pylori Antibodies and Serum Pepsinogen: A 5-Year Longitudinal Study - Min-Sun Kwak; Goh Eun Chung; Su Jin Chung; Seung Joo Kang; Jong In Yang; Joo Sung Kim (Gastroenterology Research and Practice)
Background. Helicobacter pylori (HP) and gastric atrophy are risk factors for gastric cancer. We evaluated whether the combination of serum HP antibody and pepsinogen (PG), which is indicative of gastric atrophy, could serve as a predictive marker for the development of gastric neoplasms in a Korean population. Methods. The subjects who had undergone health-screening examination with endoscopic follow-ups were classified into the following 4 groups according to serum PG status and HP antibody at baseline: group A (HP (−), normal PG), group B (HP (+), normal PG), group C (HP (+), atrophic PG), and group D (HP (−), atrophic PG). We compared the development of gastric neoplasms among the groups. Results. Of the 3297 subjects, 1239 (37.6%) were categorized as group A, 1484 (45.0%) as group B, 536 (16.3%) as group C, and 38 (1.2%) as group D. During the 5.6 years of mean follow-up period, the annual incidence of gastric neoplasms increased gradually by 0.06% in group A, 0.16% in group B, 0.38% in group C, and 0.49% in group D. A Cox proportional hazard model showed increased development of gastric neoplasms according to group (P for trend = 0.025). Compared to group A, the hazard ratio was 8.25 for group D (95% confidence interval 0.2–74.24), 5.35 for group C (1.68–17.05), and 2.65 for group B (0.86–8.14). Conclusion. The combination of serum PG and HP antibody is useful for predicting the development of gastric neoplasms, including cancer and adenoma, in a Korean population using endoscopic surveillance.